PECULIARITIES OF TEACHING ENGLISH FOR PROFESSIONAL PURPOSES TO LAW STUDENTS - Рідель, Тетяна (SWorldJournal, 2025)
The article examines the peculiarities of teaching English for professional purposes to law students. Particular attention is paid to the necessity for future lawyers to master a foreign language as a tool for professional communication in the context of